Technological Aptitude and Sensitivity of Lactic Acid Bacteria Leuconostoc Isolated from Raw Milk of Cows: From Step-by-Step Experimental Procedure to the Results - Nora Hamdaoui; Yahya Rokni; Abdeslam Asehraou; Mohamed Mouncif; Zakaria Mennane; Abdelouadoud Omari; Asmae Sellam; Belkheir Hammouti; Mustapha Meziane (Universitas Pendidikan Indonesia, 2023)
We demonstrated several technological aptitudes and sensitivity of lactic acid bacteria (Leuconostoc) isolated from the raw milk of cows. We explained the experiments in detail to get the reader to understand what kinds of technology can be used for testing bacteria. Lactic acid bacteria are used in the production of dairy products to increase their shelf life and improve their organoleptic and nutritional properties. Leuconostocs is a heterofermentative bacterium that produces lactic acid, acetic acid or ethanol, and carbon dioxide. A collection of 138 strains of lactic acid bacteria were isolated from the raw milk of cows in the region of eastern Morocco. 38 strains were identified as Leuconostocs. Their subspecies are 16 Mesenteroides, 11 Dextranicum, and 11 Cremoris. Our study was interested in the technological aptitude of this genus looking for the production of dextran and growth in milk with additional sunflower dye, as well as the acidifying, flavoring, thickening, coagulating, proteolytic activity in solid medium and Lipolytic activity. This work also consisted of studying the profile of the resistance and the sensitivity of these strains to antibiotics.